(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
Grounded environmental management training / education basic principles and approaches e.g.: complexity and wholity of spectrum for environmental management content, particularly nature and social environment interaction; interlinkage of biotic, abiotic, anthropological and communicational structures; complimentarily of state / public, household and municipal and corporate, as well as regional and international environmental management dimensions; functionality of strategic / policy and planning, programming and projecting (4P) levels of environmental management; disciplinarization and integration of environmental management realizations; necessity of environmental awareness development of specialists and public through environmental communication - information, education, participation and environmentally friendly behavior, applicability of monitoring, evaluation, planning and decision making realization functions of environmental management.